Suppose that the functions r and s are defined for all real numbers x as follows.
r(x)=x+3
s(x) = 2x
Write the expressions for (r-s) (x) and (-s) (x) and evaluate (r+s) (-1).

Suppose that the functions r and s are defined for all real numbers x as follows rxx3 sx 2x Write the expressions for rs x and s x and evaluate rs 1 class=

Respuesta :

Step-by-step explanation:

as explained in the other question : when applying an arithmetic operation on functions, you are applying it on the functional expressions.

(r*s)(x) = (x+3)*(2x²) = 2x³ + 6x²

(r-s)(x) = (x+3) - (2x²) = -2x² + x + 3

(r+s)(-1) = (-1 + 3) + (2×(-1)²) = 2 + 2×1 = 4